Design and Implementation of Multiphase Digital Oscillator - Thitaphan Jongsataporn; Poonna Yospanya; Sorawat Chivapreecha (My University, 2024)
This paper presents a design and implementation of the multiphase digital oscillator, which can determine the initial phase of multi-output signals to desired initial phases. The proposed system consists of biquad digital oscillator to oscillate the reference signal, and the new phase shifters which are first order IIR filters that can shift the phase of signals at a specified frequency to give them the desired phases. Design example and simulation results will be shown. Moreover, real-time hardware implementation on STM32 digital signal processor can be demonstrated to confirm the proposed design can work with hardware experimental results.
Keywords: Advanced Computational Techniques and Applications; Embedded Systems and FPGA Design; Sensor Technology and Measurement Systems